1999
DOI: 10.1161/01.hyp.33.3.869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coffee on Ambulatory Blood Pressure in Older Men and Women

Abstract: Abstract-This study assessed the effects of regular coffee drinking on 24-hour ambulatory blood pressure (ABP) in normotensive and hypertensive older men and women. Twenty-two normotensive and 26 hypertensive, nonsmoking men and women, with a mean age of 72.1 years (range, 54 to 89 years), took part in the study. After 2 weeks of a caffeine-free diet, subjects were randomized to continue with the caffeine-free diet and abstain from caffeine-containing drinks or drink instant coffee (5 cups per day, equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 21 publications
1
38
0
4
Order By: Relevance
“…Coffee, caffeine and blood pressure M-L Nurminen et al Rakic et al (1999) 26 54 ± 89 Instant coffee 5 cups 2 weeks Mean 24 h SBP and DBP was 4.8 and 3.0 Caffeine-free diet 2 weeks mmHg higher in coffee drinkers than in abstainers SBP, systolic blood pressure; DBP, diastolic blood pressure.…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 98%
See 3 more Smart Citations
“…Coffee, caffeine and blood pressure M-L Nurminen et al Rakic et al (1999) 26 54 ± 89 Instant coffee 5 cups 2 weeks Mean 24 h SBP and DBP was 4.8 and 3.0 Caffeine-free diet 2 weeks mmHg higher in coffee drinkers than in abstainers SBP, systolic blood pressure; DBP, diastolic blood pressure.…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 98%
“…The effects of repeated caffeine intake have also been studied in controlled studies using continuous ambulatory monitoring to measure blood pressure (Table 4). Some of the long-term studies have shown that caffeine induced persistent pressor effects (by 3 ± 6 mmHg) in habitual consumers (Ammon et al, 1983;Burr et al, 1989;James, 1994;Rakic et al, 1999). Changing from caffeinated to decaffeinated coffee (van Dusseldorp et al, 1989;Superko et al, 1994) or abstinence from coffee (Bak & Grobbee, 1990;Superko et al, 1994) resulted in a slight fall (by 2 ± 5 mmHg) in blood pressure.…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…Caffeine and risk of hypertension is another unresolved issue; whereas coffee or caffeine acutely increases blood pressure (Robertson et al, 1978;Pincomb et al, 1996;Hartley et al, 2000;Corti et al, 2002), the chronic effect of coffee consumption on blood pressure is less well known. Despite the fact that tolerance may ensue in some subjects (Robertson et al, 1981;Lovallo et al, 2004), there are data that coffee consumption is associated with chronic increases in blood pressure (Jee et al, 1999;Rakic et al, 1999;Klag et al, 2002;Noordzij et al, 2005;Savoca et al, 2005).…”
Section: Introductionmentioning
confidence: 99%